Resveratrol Regulates Colorectal Cancer Cell Invasion by Modulation of Focal Adhesion Molecules - Constanze Buhrmann (Nutrients, 2017)
Resveratrol, a safe and multi-targeted agent, has been associated with suppression of survival, proliferation and metastasis of cancer, however, the underlying mechanisms for its anti-cancer activity, particularly on cellular signaling during cancer cell migration still remain poorly understood. We investigated the invasion response of two human colorectal cancer (CRC) cells (HCT116 and SW480) to resveratrol and studied the effect of specific pharmacological inhibitors, cytochalasin D (CytD) and focal adhesion kinase-inhibitor (FAK-I) on FAK, cell viability and migration in CRC. We found that resveratrol altered cell phenotype of both CRC cells, reduced cell viability and the results were comparable to FAK-I and CytD. These effects of resveratrol were associated with marked Sirt1 up-regulation, FAK down-regulation, inhibition of focal adhesion and potentiation of effects by combinatorial treatment of resveratrol and inhibitors. Interestingly, inhibition of FAK with FAK-I or treatment with CytD suppressed resveratrol-induced Sirt1 up-regulation and markedly down-regulated FAK expression. Resveratrol or combination treatment with inhibitors significantly activated caspase-3 and potentiated apoptosis. Moreover, resveratrol suppressed invasion and colony forming capacity, cell proliferation, β1-Integrin expression and activation of FAK of cells in alginate tumor microenvironment, similar to FAK-I or CytD. Finally, we demonstrated that resveratrol, FAK-I or CytD inhibited activation of NF-κB, suppressed NF-κB-dependent gene end-products involved in invasion, metastasis, and apoptosis; and these effects of resveratrol were potentiated by combination treatment with FAK-I or CytD. Our data illustrated that the anti-invasion effect of resveratrol by inhibition of FAK activity has a potential beneficial role in disease prevention and therapeutic management of CRC.